Association of lung clearance index with survival in individuals with cystic fibrosis. Issue 3 (3rd March 2022) - Kurz, Johanna Manuela; Ramsey, Kathryn Angela; Rodriguez, Romy; Spycher, Ben; Fischer Biner, Reta; Latzin, Philipp; Singer, Florian
Background: The lung clearance index (LCI) assesses global ventilation inhomogeneity and is a sensitive biomarker of airway function in cystic fibrosis (CF) lung disease. We examined the association of LCI with the risk of death or lung transplantation (LTx) in individuals with CF. Methods: We performed a retrospective analysis in a cohort of individuals with CF aged ≥5 years with LCI and forced expired volume in 1 s (FEV1 ) measurements performed between 1980 and 2006. The outcome was time until death or LTx. We used the earliest available LCI and FEV1 values in a Cox proportional hazards regression adjusted for demographic and clinical variables. For sensitivity analyses, we used the mean of the first three LCI and FEV1 measurements, stratified the cohort based on age, and investigated individuals with normal FEV1 . Results: In total, 237 individuals with CF with a mean (range) age of 13.9 (5.6–41.0) years were included. The time-to-event analysis accrued 3813 person-years and 94 (40%) individuals died or received LTx. Crude hazard ratios were 1.04 (95% CI 1.01–1.06) per 1.0 z-score increase in LCI and 1.25 (95% CI 1.11–1.41) per 1.0 z-score decrease in FEV1 . After adjusting LCI and FEV1 mutually in addition to sex, age, body mass index and number of hospitalisations, hazard ratios were 1.04 (95% CI 1.01–1.07) for LCI and 1.12 (95% CI 0.95–1.33) for FEV1 . Sensitivity analyses yielded similar results and using the mean LCI strengthened the associations. Conclusions: Increased ventilation inhomogeneity is associated with greater risk of death or LTx. Our data support LCI as novel surrogate of survival in individuals with CF. The lung clearance index (LCI) is a measure of global ventilation inhomogeneity that increases early during the course of cystic fibrosis (CF) lung disease. This study shows that LCI is associated with death or lung transplantation in individuals with CF. https://bit.ly/2T3ia9C